1991
DOI: 10.1136/jcp.44.10.820
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated pneumocystis carinii infection in AIDS.

Abstract: Eight patients with AIDS and Pneumocystis carinii infection were studied. Protean manifestations were a feature not untypical of disseminated pneumocystosis. Aerosolised pentamidine as prophylaxis against P carinni pneumonia was ineffective at suppressing dissemination. The knowledge that extrapulmonary infection can occur has implications for the detection and treatment of, and prophylaxis against, P carinji infection. The survival of patients with disseminated pneumocystosis is particularly poor, and may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 18 publications
0
16
0
4
Order By: Relevance
“…Todos ellos con inmunocompromiso grave 1,13 . La mayoría de los casos descritos son durante la década de los 90s, en los cuales no era claro si los pacientes VIH en etapa SIDA eran más susceptibles a una diseminación extrapulmonar que otros pacientes con riesgo de neumonía por P. jiroveci 13,14 . Sin embargo, tres factores podrían tener importancia, el primero es que los pacientes con infección por VIH logran sobrevivir más tiempo y pueden llegar a etapas de mayor inmunocompromiso.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Todos ellos con inmunocompromiso grave 1,13 . La mayoría de los casos descritos son durante la década de los 90s, en los cuales no era claro si los pacientes VIH en etapa SIDA eran más susceptibles a una diseminación extrapulmonar que otros pacientes con riesgo de neumonía por P. jiroveci 13,14 . Sin embargo, tres factores podrían tener importancia, el primero es que los pacientes con infección por VIH logran sobrevivir más tiempo y pueden llegar a etapas de mayor inmunocompromiso.…”
Section: Discussionunclassified
“…Se ha descrito compromiso de pabellón auricular, coroides, retina, tiroides, paratiroides, hígado, bazo, páncreas, riñón, uréteres, glándulas adrenales, corazón, tráquea, ganglios linfáticos, pleura, líquido ascítico, orina, médula ósea, músculos, hipófisis, meninges, corteza cerebral, tracto gastrointestinal, incluyendo un caso de perforación de intestino delgado 17 . El sitio más frecuente de compromiso extrapulmonar corresponde a los ganglios linfáticos [6][7][8][9][10][11][12][13][14][15][16] . La vía de diseminación puede ser hematógena, linfática, y también por contigüidad como en casos descritos de neumonía por P. jiroveci con derrame pleural concomitante [6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…4 Some studies have suggested that the disseminated form of Pneumocystis infection is associated with CMV coinfection. 8 Our patient had no known history of P jiroveci pneumonia and had not used aerosolized pentamidine. The relationship between extrapulmonary pneumocystosis and aerosolized pentamidine is somewhat complex.…”
Section: Pathology Findingsmentioning
confidence: 99%